ASSOCIATION BETWEEN HANDGRIP STRENGTH AND INFLAMMATION IN HEMODIALYSIS PATIENTS - Viviane O Leal; Milena B Stockler-Pinto; Julie C Lobo; Najla E Farage; Luiz A Anjos; Denise Mafra (The Korean Society of Nephrology, 2012)
The inflammation is a common feature in HD patients and may contribute to muscle wasting. Handgrip strength (HGS) has been recognized as a useful tool in assessing muscle function in hemodialysis (HD) patients. The aim of this study was to evaluate the association between inflammation and muscle function in HD patients. Twenty-three HD patients (19 men, 54.3±12.4 years of age, BMI, 24.5±4.6kg/m2) were studied. HGS was measured 3x with a mechanical dynamometer after the HD sessions. HGS values less than the 10th percentile of an age-, gender- and regional specific reference were considered as muscle function loss. Tumoral necrosis factor-α (TNF-α) and interleukin-6 (IL-6) levels were determined by a multiplex assay kit through the device Luminex method. C-reactive protein (CRP) was measured with the immunoturbidimetric method. HGS values were significantly greater in males (28.8±9.7 kg) than females (13.9±6.5kg) (p <0.0001) and, 57.6% of the HD patients presented muscle function loss. TNF-α, IL-6 and CRP levels were 5.6±1.7pg/mL, 3.5 (1.75) pg/mL and 0.17 (0.50) mg/dL, respectively. According to the CRP levels, 42.4% of the HD patients presented inflammation (CRP > 0.3mg/dL). CRP and IL-6 were not correlated with HGS, but TNF-α were inversely correlated with HGS (r =-0.42; p = 0.01). These data suggest that inflammation can play an important role on muscle function in HD patients.fx1